2021
DOI: 10.1097/wnr.0000000000001577
|View full text |Cite
|
Sign up to set email alerts
|

Memantine protects blood–brain barrier integrity and attenuates neurological deficits through inhibiting nitric oxide synthase ser1412 phosphorylation in intracerebral hemorrhage rats: involvement of peroxynitrite-related matrix metalloproteinase-9/NLRP3 inflammasome activation

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…We detected hyperphosphorylation events in the flavin mononucleotide–binding domain in the SON and NIL as a result of WD, where increased phosphorylation at S847 in the NIL, but not the SON, has been shown to reduce NOS1 activity by inhibiting the binding of Ca 2+ to the calmodulin domain ( 73 , 74 ). In addition, NOS1 phosphorylation at S1412 in the NADPH-binding domain (hyperphosphorylated in SON, but not NIL) has been shown to increase the activity of NOS1 ( 75 , 76 ). It has been suggested that hyperosmotic stimulation induces NO production in MCNs in the SON ( 77 , 78 ), reducing AVP and OXT secretion as a feedback compensatory mechanism to prevent oversecretion of these peptides ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…We detected hyperphosphorylation events in the flavin mononucleotide–binding domain in the SON and NIL as a result of WD, where increased phosphorylation at S847 in the NIL, but not the SON, has been shown to reduce NOS1 activity by inhibiting the binding of Ca 2+ to the calmodulin domain ( 73 , 74 ). In addition, NOS1 phosphorylation at S1412 in the NADPH-binding domain (hyperphosphorylated in SON, but not NIL) has been shown to increase the activity of NOS1 ( 75 , 76 ). It has been suggested that hyperosmotic stimulation induces NO production in MCNs in the SON ( 77 , 78 ), reducing AVP and OXT secretion as a feedback compensatory mechanism to prevent oversecretion of these peptides ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…We detected hyperphosphorylation events in the flavin mononucleotide (FMN)-binding domain in the SON and NIL as a result of WD, where increased phosphorylation at S847 in the NIL, but not the SON, has been shown to reduce NOS1 activity by inhibiting the binding of Ca 2+ to the calmodulin domain (Hayashi et al, 1999; Komeima et al, 2000). In addition, NOS1 phosphorylation at S1412 in the NADPH-binding domain (hyperphosphorylated in SON, but not NIL) has been shown to increase the activity of NOS1 (Chen et al, 2021; Khan et al, 2015). It has been suggested that hyperosmotic stimulation induces NO production in MCNs in the SON (da Silva et al, 2013; Reis et al, 2015) reducing AVP and OXT secretion as a feedback compensatory mechanism to prevent over-secretion of these peptides (Pires da Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, pioglitazone, edaravone and adiponectin significantly reduced brain edema and attenuated neurological deficits after ICH, as well as decreased the expression of IL-1β, IL-18, caspase-1 and NF-κB through suppressing the expression of NLRP3 [8,28,29]. Glibenclamide markedly reduced the neurological deficit and brain edema after ICH by decreasing the expression of ASC and caspase-1 and suppressing the activation of the NLRP3 inflammasome to maintain BBB integrity [30]. Memantine reduces ONOO-production by inhibiting neuronal nitric oxide synthase (nNOS) phosphorylation at ser1412, which further inhibits MMP-9 expression and NLRP3 inflammasome activation, protecting the blood-brain barrier integrity and alleviating neurological deficits in ICH rats [31].…”
Section: Modulation Of Nlrp3 Inflammasome Activity As a Therapeutic S...mentioning
confidence: 98%